Unmasking the invaders: NLR-mal function in plant defense - Anbu, Susanna; Swart, Velushka; van den Berg, Noëlani (Frontiers in Plant Science, 2023)
Plants possess an arsenal of immune receptors to allow for numerous tiers of defense against pathogen attack. These immune receptors can be located either in the nucleocytoplasm or on the plant cell surface. NLR gene clusters have recently gained momentum owing to their robustness and malleability in adapting to recognize pathogens. The modular domain architecture of an NLR provides valuable clues about its arms race with pathogens. Additionally, plant NLRs have undergone functional specialization to have either one of the following roles: to sense pathogen effectors (sensor NLRs) or co-ordinate immune signaling (helper or executer NLRs). Sensor NLRs directly recognize effectors whilst helper NLRs act as signaling hubs for more than one sensor NLR to transduce the effector recognition into a successful plant immune response. Furthermore, sensor NLRs can use guard, decoy, or integrated decoy models to recognize effectors directly or indirectly. Thus, by studying a plant host's NLR repertoire, inferences can be made about a host's evolutionary history and defense potential which allows scientists to understand and exploit the molecular basis of resistance in a plant host. This review provides a snapshot of the structural and biochemical properties of the different classes of NLRs which allow them to perceive pathogen effectors and contextualize these findings by discussing the activation mechanisms of these NLR resistosomes during plant defense. We also summarize future directives on applications of this NLR structural biology. To our knowledge, this review is the first to collate all vast defense properties of NLRs which make them valuable candidates for study in applied plant biotechnology.